Critical and subcritical fractional Hamiltonian systems of Schrödinger equations with vanishing potentials. (April 2023) - Miyagaki, O.H.; Santana, C.R.; Toon, E.; Ubilla, P.
Abstract: We analyze a class of fractional Hamiltonian systems of Schrödinger equations in R N involving vanishing potential with critical and subcritical nonlinearity. We make use of variational methods to prove the existence of at least one pair of positive solutions. Our result in the critical case is new even for the Laplacian operator.